2019
DOI: 10.1021/acssuschemeng.8b03818
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of the Glycerol-Embedded Hybrid Coal

Abstract: The molasses embedded hybrid coal (Hybrid Coal by Korea Institute of Energy Research; HCK) was previously proposed as an attractive alternative to low-rank coals that tend to show low calorific values and high CO2 emissions. HCK was synthesized by mixing molasses with a low-rank coal to enhance its heating value. Nevertheless, food ethics regarding molasses additives still have impeded its commercial acceptance. In this study, we propose a glycerol (nonfood)-based coal upgrading process to improve the combusti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…These characteristics can be confirmed indirectly from the DTG graph ( Figure 2). The combustion boundary of VM and FC changed broadly, and the complete combustion of FC proceeded [38]. CO and C x H y emissions and unburned carbon (UBC) are closely related.…”
Section: Air Pollutants Emissions Of Hsfmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics can be confirmed indirectly from the DTG graph ( Figure 2). The combustion boundary of VM and FC changed broadly, and the complete combustion of FC proceeded [38]. CO and C x H y emissions and unburned carbon (UBC) are closely related.…”
Section: Air Pollutants Emissions Of Hsfmentioning
confidence: 99%
“…These results are in good agreement with those of a previous study. According to Lee [41] and Park [38], biomass-impregnated fuels improve combustion responsiveness and reduce UBC emissions. Therefore, HSF with lignin would be beneficial for application in power plants from an environmental perspective in terms of particulate matter emission reduction.…”
Section: Air Pollutants Emissions Of Hsfmentioning
confidence: 99%
“…In paper, 23 it is shown that the addition of glycerol directly to low‐grade coal leads to an improvement in combustion kinetics, a reduction in unburned carbon emissions by 35%, and an increase in the calorific value of such a composite fuel by 80%.…”
Section: Introductionmentioning
confidence: 99%